2001
DOI: 10.1634/stemcells.19-1-1
|View full text |Cite
|
Sign up to set email alerts
|

New Strategies in the Treatment of Acute Myelogenous Leukemia (AML): In Vitro Culture of AML Cells—The Present Use in Experimental Studies and the Possible Importance for Future Therapeutic Approaches

Abstract: In vitro studies of cultured native acute myelogenous leukemia (AML) blasts and cell lines have contributed significantly to our present knowledge about the pathogenesis of AML. In the present article we review different techniques for preparation and in vitro culture of AML blasts. Well-characterized serum-free in vitro conditions can now be used in experimental studies of AML, and this makes comparisons between different studies easier. We also describe assays for characterization of AML progenitor subsets (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
109
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 102 publications
(124 citation statements)
references
References 70 publications
5
109
0
Order By: Relevance
“…The proapoptotic properties of the proteasome inhibitors seen in assays of a few days duration mainly reflect the characteristics of the more mature majority of leukaemia cells, whereas the proliferation in suspension cultures reflects an enrichment of more immature clonogenic cells (Bruserud et al, 2001). We therefore investigated the effect of bortezomib and PR-171 for these minor subsets of AML cells: (i) the clonogenic cells that represent a small minority of the AML cell population and are regarded as less mature; and (ii) the CD34 + AML cell subset that seems to include the leukaemic stem cells (i.e.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…The proapoptotic properties of the proteasome inhibitors seen in assays of a few days duration mainly reflect the characteristics of the more mature majority of leukaemia cells, whereas the proliferation in suspension cultures reflects an enrichment of more immature clonogenic cells (Bruserud et al, 2001). We therefore investigated the effect of bortezomib and PR-171 for these minor subsets of AML cells: (i) the clonogenic cells that represent a small minority of the AML cell population and are regarded as less mature; and (ii) the CD34 + AML cell subset that seems to include the leukaemic stem cells (i.e.…”
Section: Figmentioning
confidence: 99%
“…We therefore investigated the effect of bortezomib and PR-171 for these minor subsets of AML cells: (i) the clonogenic cells that represent a small minority of the AML cell population and are regarded as less mature; and (ii) the CD34 + AML cell subset that seems to include the leukaemic stem cells (i.e. those cells responsible for long-term in vitro proliferation and repopulation in xenografted immunocompromised mice) for most patients (Bruserud et al, 2001;Bonnet, 2005;Guo et al, 2006). Our results demonstrated that bortezomib and PR-171 have antiproliferative effects on the more immature subsets within the hierarchically organised AML cell populations.…”
Section: Figmentioning
confidence: 99%
“…Expansion of AML in vitro culture systems are generally limited to immortalised cell lines, shortterm culture of primary explants and assays on clinical samples. [280][281][282] These in vitro models fail to engage decisive issues such as cellular/environmental interactions, invasiveness and angiogenesis in AML, thus necessitating development of a relevant xenotransplantation animal model.…”
Section: Xenograft Modelsmentioning
confidence: 99%
“…AML blasts were derived from 59 patients. The cells were prepared from peripheral blood samples by density gradient separation (Ficoll-Hypaque with specific density 1.077; NyCoMed, Oslo, Norway) as described in detail previously, 51 and the percentage of leukemic cells in this population exceeded 95%.…”
Section: Patient Characteristics and Sample Preparationmentioning
confidence: 99%